DEVELOPMENT OF INTERACTIVE LEARNING MEDIA NETWORK SERVICE ENGINEERING USING SOFTWARE MULTIMEDIA ADOBE FLASH CS6 - Putra Haryanto, Priangga Pratama; Suci Amalia, Hamsar; Tri Utomo, Randi (MACCA : Science-Edu Journal, 2024)
Less interactive learning media accompanied by the delivery of less interesting material can make students feel bored when participating in learning. Therefore, interactive learning media can be the right alternative to overcome these problems. One of them uses the Adobe Flash CS6 Multimedia Software. This study aims to produce interactive learning media for computer network engineering in network service engineering subjects using a valid Adobe Flash CS6 Multimedia Software. This study uses the ADDIE development model (Analysis-Desain-Develop-implementation-Evaluate) which has five stages of development including analysis, design, development, implementation, and evaluation. Validation is carried out to determine the feasibility of the developed multimedia. Validation was obtained by using data collection methods in the form of questionnaires given to material experts and media experts. The responses of students and educators were obtained by collecting data in the form of a questionnaire. The results of material expert validation obtained an average of 91.67% with the "Very Eligible" category. The overall material validity test is 88.89% with the "Very Eligible" category. Practical test of learning media was tested by 1 teacher and 16 students. Practicality for the practicality test of teachers is 87.11% and practicality by students is 79.80% so that it can be interpreted very practical to use.